(3GdCUhd hGdVhGHWs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GeG HYO agPg bhGYO hVhGHW hGUhd hegeGJ hebGUO eWdhHGJ jMJGL GdjgG WGdHhG GdePgH Hd WGdHhG GdYde eWdbkG hGdebUhO HgG HjGf GdbhGYO GdLGeYI s
(3BNQgG (B:s
(3hGdGUM ef Gdbhdjf ai eYXe GdUhQI ddCNP HGdCUd hGddg GYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B115s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B(173) s
Keywords: (3CUhd Gdabgs